(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In the realm of ultra-high sampling rates, Fast Fourier Transform (FFT) stands as a cornerstone in analyzing acoustic emission signals. This manuscript presents an efficient hardware architecture tailored for executing FFT using the radix-2 Frequency Decimation Algorithm (R2DIF) and a channelled method facilitating effective data sharing via shift registers. The architecture employs an optimal rotation method leveraging the modified Digital Coordinate Rotation Computer Algorithm (mCORDIC) and Radix-2r, dependent on the coding scheme, to replace complex multipliers in FFT computation. The integration of m-CORDIC enhances computational efficiency, while Radix-2r facilitates a logarithmic reduction in adder steps, optimizing FFT execution for ultra-high sampling rates.